How do you simplify the expression #(1+(2c^2-6c-10)/(c+7))/(2c+1)#?

1 Answer
Mar 31, 2017

Answer:

#" The Exp.="(c-3)/(c+7), if, c!=-7, c!=-1/2.#

Explanation:

#"The Exp.="{1+(2c^2-6c-10)/(c+7)}/(2c+1),#

#={(c+7+2c^2-6c-10)/(c+7)}-:(2c+1),#

#={(2c^2-5c-3)/(c+7)}-:(2c+1),#

#=[{ul(2c^2-6c)+ul(c-3)}/(c+7)]-:(2c+1),#

#=[{2c(c-3)+1(c-3)}/(c+7)]-:(2c+1),#

#=[{(c-3)(2c+1)}/(c+7)]-:(2c+1),#

#=[{(c-3)(cancel(2c+1))}/(c+7)]xx1/{cancel(2c+1)},#

#:." The Exp.="(c-3)/(c+7), if, c!=-7, c!=-1/2.#

Enjoy Maths.!